EDUCATIONAL COMPETENCE IN DIDACTICS AND METHODS OF PERSON-ORIENTED TRAINING - A.V. Khutorskiy (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the notion of educational competence, its functions, and structural components.